A Visual Diary of an Anorexic Woman: Development of a Hopeful Self-Healer Identity - Boisvert, Jennifer (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper chronicles an anorexic woman's exploration of her experience of hope in recovery. An innovative single-participant design using heuristic case study and photography was used. Content and thematic analyses of photos and journal entries/poems led to the emergence of four metaphors and themes: Opening the Shutter (liberty); Focusing the Lens (security); Framing the Image (reality); and Taking the Picture (vitality). The creation of a visual diary enhanced metaphoric self-understanding and the development of a hopeful self-healer identity. Implications for clinical training, research, and practice regarding the benefits of photographic self-exploration by clients and clinicians are discussed.